Perceived Stress and Fear of COVID-19 Among the Elderly Referred to Comprehensive Health Centers in Tehran, Iran - Farideh Bastani; Hamid Haghani (Iran University of Medical Sciences, 2022)
Background & Aims: The emerging diseases such as coronavirus disease 2019 (COVID-19) can cause a serious stress, fear, and anxiety in the elderly. This study aims to determine the perceived stress and fear of COVID-19 in the elderly referred to comprehensive health centers in Tehran, Iran. Materials & Methods: In this descriptive cross-sectional study, 260 older people aged >60 years referred to two comprehensive health centers (130 from each center)  in the west of Tehran participated, who were selected by cluster and stratified sampling methods. Data collection tools were a demographic form, the Perceived Stress Scale, and the Fear of COVID-19 Scale. Descriptive and inferential statistics were used to analyze the collected data in SPSS Software, version 20. Results: The mean score of perceived stress was 41.5±10.19, indicating high level of stress in the elderly. This variable had a statistically significant relationship with age, underlying disease, and self-perceived health (P<0.001). The results of the Scheffe post hoc test showed that perceived stress was significantly lower in married subjects, those with no underlying disease, and those with self-perceived health score of 5 or higher. Fear of COVID-19 with a mean score of 23.45±9.35, was also higher among the elderly. Conclusion: The perceived stress and fear of COVID-19 are high among the elderly in Tehran, Therefore, a proper planning by the health system policymakers for this group is necessary during the pandemic.